Inner Speech in People with Aphasia - William Hayward; Peter Ethan Turkeltaub (Frontiers in Psychology, 2014)
Introduction: Although impaired word finding—anomia—is typically observed in people with aphasia, they often report being able to internally retrieve certain words correctly, saying that “it sounds right in my head” (Marshall & Tompkins, 1982). This sense of successful Inner Speech (IS) is difficult to verify, leaving clinicians and scientists uncertain of its meaning. Previous work has shown differences in how often people report having “the idea of a word” depending on the diagnosis, and this is reflected in performance on phonological tasks (Goodglass, Kaplan, Weintraub, & Ackerman, 1976). However, this prior study did not test items on a word-by-word basis. Also, while covert (internal) naming tasks are often used in aphasia research, especially neuroimaging, no study to date has tested whether insight into IS predicts the brain networks recruited during word retrieval. Hypothesis: The self-report of subjectively correct IS (scIS) is meaningful and represents phonological access. Brain activity reflects successful phonological access. Procedures: A questionnaire investigated the sense of IS in people with aphasia. Three pilot participants who reported scIS performed a battery of neurolinguistic tests. Multiple baseline naming was used to select words that were consistently correct or incorrect out loud on 3 separate days for each individual. While in the scanner, participants named selected items internally and reported their subjective success. Two individuals underwent a 3-month course of aphasia therapy for the consistently incorrect words. Analyses: Functional imaging data were analysed according to self-reported accuracy from the participants. Results: Questionnaire: Individuals with aphasia experienced successful IS, and participants were able to distinguish between “I can say it in my head” and “I know what it is”. Imaging: For scIS, there was no difference in brain activity based on out loud success. When incorrect out loud, scIS showed significantly greater activity in superior temporal areas typically involved in phonological access than items with subjectively incorrect IS. Treatment: Items reported as scIS before treatment were learned more quickly than those reported as internally incorrect. Conclusions: Reports of scIS are common but not universal in people with aphasia. People with aphasia can discriminate between simply knowing a concept and the specific feeling of scIS. In study participants, fMRI activity corresponds with the subjective experience of IS in aphasia, including areas associated with phonological access. The treatment results suggest that insight into IS is meaningful and that self-reported IS may be clinically important because it predicts the success of subsequent therapy on a word-by-word basis. Here, we have demonstrated that subjective reports of IS are meaningful in at least some individuals with aphasia. Additional research is needed to confirm the degree to which self-reported IS accurately reflects phonological access, as well as to determine which processes of word retrieval and self-monitoring are needed for reliable insights into inner speech and how specific language deficits interact with these insights. Examining insight into IS could inform our understanding of the psychological and neural bases of word retrieval as well as provide a novel tool for early prognosis and individualized aphasia treatment.